Comparative Analysis of the MPPT Algorithm in a Residence and a Grid-Connected Solar PV System Under Partial Shade Conditions - A Review - Dodaev, Zohar Al; Aziz, Tareq; Rahman, Md. Shahriar; Joy, Tamal Ahammed (Peneliti Teknologi Teknik Indonesia, 2024)
The abstract gives a clear overview of the study's aims, techniques, and conclusions. The authors compare Maximum Power Point Tracking (MPPT) algorithms in two different solar photovoltaic (PV) system setups such as a home system and a grid-connected system, both running in partial shade. The study's goal is to review the performance of various MPPT algorithms in these settings and provide insights into their effectiveness in improving energy extraction from PV panels. The authors evaluate and assess various MPPT approaches and their adaptation to various system settings using tracking efficiency and conversion efficiency. This can be evaluated through algorithmic complexity analysis, hardware implementation considerations, and simulation studies using software tools like MATLAB/Simulink or PSpice. The paper explores the impact of partial shade on solar PV systems and its implications for energy output using a complete evaluation of relevant literature and empirical data. The authors evaluate the feasibility of MPPT algorithms for reducing the negative impacts of partial shading, concentrating on their capacity to track the maximum power point of the panels rapidly and correctly. The review also takes into account system efficiency, response time, and computing complexity. The findings of this study offer valuable insights into the performance of MPPT algorithms in the context of residential and grid-connected solar PV systems operating under partial shade conditions. The authors highlight the strengths and limitations of different MPPT techniques and provide recommendations for selecting appropriate algorithms based on the specific application. The comparative analysis sheds light on the challenges posed by partial shading and underscores the importance of advanced MPPT strategies in improving the overall efficiency and energy yield of solar PV systems. Overall, this paper contributes to the understanding of MPPT algorithms' role in enhancing solar energy utilization in both residential and grid-connected settings, particularly when dealing with partial shade scenarios.